Managing facilities - Jones, Christine. (Butterworth-Heinemann, 1998)
This book is about: The concepts and scope of facilities management; The strategic planning role; The physical assets; Provision and specification of facilities services; Designing the facilities services operation delivery system; Investing in staff; ...